Proceedings of international conference on soft computing techniques and engineering application : ICSCTEA 2013, September 25-27, 2013, Kunming, China - Patnaik, Srikanta; Li, Xiaolong (Advances in Intelligent Systems and Computing, 2014)
The main objective of ICSCTEA 2013 is to provide a platform for researchers, engineers and academicians from all over the world to present their research results and development activities in soft computing techniques and engineering application. This conference provides opportunities for them to exchange new ideas and application experiences face to face, to establish business or research relations and to find global partners for future collaboration.